Odpowiedzi

2010-01-21T15:21:40+01:00
A)
{4x-5y= -4
{-2x+3y=1,1 /×2
{4x-5y=-4
+ {-4x+6y=2,2
-----------------
4x-5y-4x+6y=-1,8
y=-1,8 y=-1,8
4x-5×(-1,8)=-4
4x+9=-4 /-9
4x=- 13/ :4
x= -3,25
2010-01-21T15:25:23+01:00
A)
4x-5y= -4|*3
-2x+ 3y=1,1|*5

12x-15y=-12
-10x+15y=5,5
2x=-6,5
x=-3,25

4*(-3,25)-5y=-4
-13-5y=-4
-5y=9
y=-1,8

b)
-2x+y=0|*3
3x-3y=1

-6x+3y=0
3x-3y=1
-3x=1
x=-1/3

-2*(-1/3)+y=0
2/3+y=0
y=-2/3

c)
3x-2y=-12|*(-5)
2x-5y=-19|*2

-15x+10y=60
4x-10y=-38
-11x=22
x=-2

3*(-2)-2y=-12
-6-2y=-12
-2y=-6
y=3